2006
DOI: 10.1002/ajmg.b.30460
|View full text |Cite
|
Sign up to set email alerts
|

Association of the dopamine receptor D4 (DRD4) gene 7‐repeat allele with children with attention‐deficit/hyperactivity disorder (ADHD): An update

Abstract: Polymorphisms of the dopamine receptor D4 gene DRD4, 11p15.5, have previously been associated with attention-deficit/hyperactivity disorder (ADHD) [Bobb et al., 2005; Am J Med Genet B Neuropsychiatr Genet 132:109-125;Faraone et al., 2005; Biol Psychiatry 57:1313-1323Thapar et al., 2005; Hum Mol Genet 14 Spec No. 2:R275-R282]. As a follow up to a pilot study [see Castellanos et al., 1998; Mol Psychiatry 3:431-434] consisting of 41 probands and 56 controls which found no significant association between the DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…One study was excluded because the control sample did not consist of healthy individuals [Ballon et al, 2007]. Note that a number of included case-control studies reported family-based association ORs [Hawi et al, 2000;Holmes et al, 2000;Mill et al, 2001;Roman et al, 2001;Gornick et al, 2007]. In these studies, only the data from the case-control association analyses were reported as they were associated with more precise sample information, included more participants, and are comparable to family-based results [Evangelou et al, 2006].…”
Section: Identified Studiesmentioning
confidence: 99%
“…One study was excluded because the control sample did not consist of healthy individuals [Ballon et al, 2007]. Note that a number of included case-control studies reported family-based association ORs [Hawi et al, 2000;Holmes et al, 2000;Mill et al, 2001;Roman et al, 2001;Gornick et al, 2007]. In these studies, only the data from the case-control association analyses were reported as they were associated with more precise sample information, included more participants, and are comparable to family-based results [Evangelou et al, 2006].…”
Section: Identified Studiesmentioning
confidence: 99%
“…This familial aggregation is believed to be partially explained by genetic factors, as the heritability of ADHD has been reported to be between 75 and 91% (Faraone et al, 2005;Thapar et al, 2006;Masellis et al, 2006). Numerous vulnerability genes have been proposed in ADHD with some convergence for gene coding for the dopamine receptor D4 (Faraone et al, 2005;Gornick et al, 2007;Lasky-Su et al, 2007;Shaw et al, 2007) and the dopamine transporter (Faraone et al, 2005;Thapar et al, 2006;Masellis et al, 2006;Cook et al, 1995). The precise neurochemical pathophysiology of ADHD remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…1 We recently also replicated this association, finding a significantly increased frequency of the 7-repeat allele in 169 children with ADHD (23%) compared with 265 healthy controls (17%). 2 Previous studies have suggested that carriers of the risk allele may also have a unique neuropsychological, [3][4][5][6] clinical, [7][8][9][10][11][12][13] and pharmacological 14 profile, although there remains considerable debate over the exact nature of this phenotype. The DRD4 7-repeat allele has also been linked with clinical outcome, albeit with divergent results.…”
mentioning
confidence: 99%